Genetic aspects of growth, feed efficiency and effects of selection on these traits in mice: a review - Orhan ÇETİN (Eurasian Journal of Veterinary Sciences)
A review is presented of the genetic of growth, effects of long and short-term selection experiment under different feeding regimes on weight gain, feed efficiency and food consumption in mice. The genetic parameters considered are; nature and extend of within and beetwen line genetic variation for body weight and growth rate; correlated response to se!ection for body weight, weight gain, fe ed intake and fe ed efficiency. The relationsphips of fe ed efficiency with other traits is reviewed at length. The response of characters to se!ection in the short-term differ qualitatively from those in the Jang term. In the short term, the respanses depend on genetic corre!ations between characters, but in the Jang- term they are only determined by fitness function of natural and directional selection, indepent of genetic and phenotypic corre!ations.